Neuromuscular Diseases Care in the Era of COVID-19 - Bertran Recasens, Bernat; Rubio, Miguel Angel (Frontiers in Neurology, 2020)
The COVID-19 pandemic has pushed health systems to their limit and forced readjustment of standards of care for different pathologies. Management of neuromuscular diseases becomes a challenge since most of them are chronic, disabling, progressive and/or require immunosuppressive drugs. There are three main aspects of COVID-19 that affect neuromuscular diseases care. The first one relates to how SARS-CoV2 directly affects different neuromuscular pathologies. Respiratory weakness, as seen in myasthenia gravis, amyotrophic lateral sclerosis and myopathies, and the use of immunomodulatory drugs (Myasthenia Gravis and Chronic Inflammatory Demyelinating Polyneuropathy ) make this group of patients potentially more vulnerable Secondly, safety measures also affect proper care, limiting care continuity and physical rehabilitation (one of the essential aspects of myopathies treatment). Telemedicine can partially solve the problem allowing for a continuum of close care, avoiding unnecessary visits, and even guaranteeing the attention of professionals from tertiary care centers. However, one of the crucial steps in neuromuscular diseases is diagnosis, and in most scenarios, more than one face-to-face visit is needed. Lastly, the global Covid19 situation will also have an economic impact on patients and their families. This situation is of particular concern given that neuromuscular diseases already present difficulties due to the scarcity of resources in terms of public healthcare and research.